The Influence of Computer Learning Media on the Science Ability of Children Ages 5-6 Years in Kindergarten - Herman Herman; Herlina Herlina; Sitti Nurhidayah Ilyas; Herman (Universitas Negeri Makassar, 2022)
Abstract. The problem in this research is how is the description of children's science skills through the use of computer learning media? The purpose of this study was to describe the effect of computer learning media on children's science skills. Computer-based learning media is used to stimulate children's scientific skills. This research approach is quantitative using experimental methods with research design Non-equivalent Control Group Design. Measurements were made by involving two groups, namely the experimental group and the control group. Data collection techniques were carried out through tests and documentation in the form of photos of learning activities and plans for daily learning. The data analysis technique used is descriptive statistical analysis and non-parametric statistical analysis, using the Wilcoxon Signed Rank Test analysis. Then based on this analysis, it was found that the value of T count (55) > T table (8) and the value of Z count (2.80) > Z table (1.645) means that there is an influence of computer media on the scientific abilities of children aged 5-6 years in PAUD Terpadu Teratai, Makassar.